2019
DOI: 10.1021/acs.inorgchem.8b03471
|View full text |Cite
|
Sign up to set email alerts
|

Thermostructural Behavior in a Series of Lanthanide-Containing Polyoxotungstate Hybrids with Copper(II) Complexes of the Tetraazamacrocycle Cyclam: A Single-Crystal-to-Single-Crystal Transformation Study

Abstract: The series of fourteen isostructural [Cu(cyclam)]2[{Cu(cyclam)}4{(α-GeW11O39)Ln(H2O)(OAc)}2]•18H2O (1-Ln, Ln = La to Lu; cyclam = 1,4,8,11-tetraazacyclotetradecane) polyoxometalate-based hybrids reported herein represent: (i) the first example of a 2-dimensional covalent hybrid lattice involving the [{(α-XW11O39)Ln(H2O)(OAc)}2] narchetype; and (ii) the first structural characterization of such dimeric polyoxotungste for Ln = La and Pr, as well as for the combination of X = Ge and Ln = Ce, Nd, Sm or Lu. Compoun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 62 publications
(117 reference statements)
0
14
0
Order By: Relevance
“…Single crystals of 1 were slowly heated in an oven at a rate of 1 °C min −1 up to 50, 70, and 100 °C and subsequently quenched to 100 K to determine whether high temperature phases found in variable temperature PXRD studies can be analyzed by this technique. In contrast to our latest reports on POM/{Cu(cyclam)} systems, 21,22 the single crystallinity is not preserved upon evacuation of water molecules, and hence, it prevented us from performing scXRD experiments on thermally activated samples. We tried to overcome these difficulties by dehydrating crystals of 1 under vacuum (P = 10 −5 Pa) at room temperature for 1 h, and luckily, we were able to carry out a full data acquisition for the anhydrous 2 at 100 K. In fact, the PXRD pattern of 1 exposed to high vacuum is virtually identical to both the PXRD pattern recorded at 100 °C and the simulated one from the single crystal data for 2 (Figure 1b).…”
Section: ■ Experimental Sectionmentioning
confidence: 64%
See 3 more Smart Citations
“…Single crystals of 1 were slowly heated in an oven at a rate of 1 °C min −1 up to 50, 70, and 100 °C and subsequently quenched to 100 K to determine whether high temperature phases found in variable temperature PXRD studies can be analyzed by this technique. In contrast to our latest reports on POM/{Cu(cyclam)} systems, 21,22 the single crystallinity is not preserved upon evacuation of water molecules, and hence, it prevented us from performing scXRD experiments on thermally activated samples. We tried to overcome these difficulties by dehydrating crystals of 1 under vacuum (P = 10 −5 Pa) at room temperature for 1 h, and luckily, we were able to carry out a full data acquisition for the anhydrous 2 at 100 K. In fact, the PXRD pattern of 1 exposed to high vacuum is virtually identical to both the PXRD pattern recorded at 100 °C and the simulated one from the single crystal data for 2 (Figure 1b).…”
Section: ■ Experimental Sectionmentioning
confidence: 64%
“…In order to determine whether 1 is able to exhibit a comparable thermostructural behavior to that displayed by related {Cu­(cyclam)} 2+ /POM systems in which the crystallinity is retained all along the dehydration process, ,,, VT-PXRD analyses were performed from room temperature to 600 °C (Figure S5). These studies showed that our hybrid compound is able to maintain its crystallinity up to 250 °C, which is in good agreement with the thermal stability range observed in TGA measurements.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…When [RE( α -PW 11 O 39 ) 2 ] (RE = Ce III , Pr III ) dimers were connected by [Cu(en)(2,2′-bipy)] 2+ and [Cu(en) 2 ] 2+ , a 1D zigzag chain was formed whilst strong hydrogen bonding constructed a 2D lattice [ 196 ]. Another interesting example was observed in a series of some isostructural [Cu(cyclam)] 2 [{Cu(cyclam)} 4 {( α -GeW 11 O 39 )RE(H 2 O)(OAc)} 2 ]·18H 2 O (RE = La−Lu) hybrids where acetate ions connected two {( α -GeW 11 O 39 )RE} polyanions, while three type {Cu(cyclam)} 2+ moieties had different structural roles: surface-appended antenna unit, linking moieties, and charge-balancing cation [ 197 ].…”
Section: Inorganic–organic Hybrids Based On Pbtrehd With Mixed Organic Ligandsmentioning
confidence: 99%